The Lays of Marie de France - Translated by David R. Slavitt (Mingling Voices, 2013)
The twelve ÒlaysÓ of Marie de France, the earliest known French woman poet, are here presented in sprightly English verse by poet and translator David R. Slavitt. Traditional Breton folktales were the raw material for Marie de FranceÕs series of lively but profound considerations of love, life, death, fidelity and betrayal, and luck and fate. They offer acute observations about the choices that women make, startling in the late twelfth century and challenging even today. Combining a womanÕs wisdom with an impressive technical bravura, the lays are a minor treasure of European culture.